Penggunaan Teknologi Dron dalam Fasa Projek Pembinaan - Azme, Nor Aqidah; Yahya, Mohd Yamani (Research in Management of Technology and Business, 2021)
Abstract: Drone technology is a technology that can help improve quality in the Malaysian construction industry. However, the use of drones in the construction industry throughout Malaysia is still at an early stage and is especially low in the construction phase. Therefore, the objectives of this study are to identify the use of drone technology in the project, identify the factors and barriers that hinder the use of this technology, and methods that can be taken to increase the use of drone technology in the construction industry. The qualitative study was used by carrying out a structured gathering session with three (3) industry players who were directly involved with the use of drones in the construction industry. The data was analysed using Content Analysis. The findings showed that the use of drone technology in the construction projects is still new and is being actively improved. The main barriers of drone implementation were risks of accident, drone operation, and resistance to weather. In addition, methods that may be taken to further increase the use of drone technology such as initiatives from the company, improvements to the law on the use of drone technology in Malaysia, and enhancement of battery resistance for longer use. This study can become a principle for all parties involved to increase the use of drones in the Malaysian construction industry in the future.